2017
DOI: 10.1016/j.bbadis.2016.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectrometry analysis shows the biosynthetic pathways supported by pyruvate carboxylase in highly invasive breast cancer cells

Abstract: We recently showed that the anaplerotic enzyme pyruvate carboxylase (PC) is up-regulated in human breast cancer tissue and its expression is correlated with the late stages of breast cancer and tumor size [Phannasil et al., PloS One 10, e0129848, 2015]. In the current study we showed that PC enzyme activity is much higher in the highly invasive breast cancer cell line MDA-MB-231 than in less invasive breast cancer cell lines. We generated multiple stable PC knockdown cell lines from the MDA-MB-231 cell line an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 26 publications
2
38
0
Order By: Relevance
“…First, our finding showed an increased expression of ACO2 in tumor tissues. 50 Besides, the data indicated that the MYC-regulated Gln anaplerosis may contribute to fueling the TCA cycle by providing 2-KG in PCa. 48 Another important route to control the flux into TCA cycle is from pyruvate.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…First, our finding showed an increased expression of ACO2 in tumor tissues. 50 Besides, the data indicated that the MYC-regulated Gln anaplerosis may contribute to fueling the TCA cycle by providing 2-KG in PCa. 48 Another important route to control the flux into TCA cycle is from pyruvate.…”
Section: Discussionmentioning
confidence: 97%
“…Using multiple stable PC knockdown cell lines and 13C 6 -glucose and 13C 5glutamine labeled mass spectrometry analysis, it was revealed that PC played important roles in the pyruvate cycling and mitochondrial biosynthesis of precursors of cellular components required for cell growth and replication in invasive breast cancer. 50 Besides, the data indicated that the MYC-regulated Gln anaplerosis may contribute to fueling the TCA cycle by providing 2-KG in PCa. The observation that glutamine transporter ASCT1 (also called SLC1A4, FC 5 1.78, p 5 0.00016), GLS and glutamate dehydrogenase GLUD1, GLUD2 (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Aspartate can be generated from pyruvate though oxaloacetate as via the action of PC, an enzyme mediating the conversion of pyruvate to oxaloacetate (Ling and Keech, 1966). Elevated PC expression and/or activity is observed in breast cancer and non-small-cell lung cancer (NSCLC) (Phannasil et al, 2017;Sellers et al, 2015). We show that PC mRNA translation is regulated via 4E-BPs and that 4E-BP1/2 ablation leads to dramatic increase in aspartate levels and reduction in sensitivity to KI and phenformin combination.…”
Section: Discussionmentioning
confidence: 91%
“…Compared with non‐cancerous tissues, PC expression is greatly enhanced in patients with non‐small cell lung cancer (NSCLC) and invasive breast cancer (BCA). [ 9 ] In early stages of NSCLC, growth inhibition by PC knockdown is accompanied by disrupted TCA activity and biosynthesis. [ 10 ] In particular, BCA accounts for the highest frequency of PC amplification according to The Cancer Genome Atlas (TCGA).…”
Section: Introductionmentioning
confidence: 99%
“…[ 11 ] Importantly, BCA lung metastases develop a significantly higher PC‐catalyzed generation of oxaloacetate, along with an increased intracellular pyruvate level as compared to primary tumors. [ 9b,12 ] Researchers also unveiled a potential metabolic vulnerability of glutamine independent cancer cells through inhibiting PC activity. [ 6c,13 ] Thus, PC could be a promising therapeutic target for cancer progression.…”
Section: Introductionmentioning
confidence: 99%